COVID-19 PANDEMIC: LEADERSHIP SKILLS FIT FOR THE FUTURE - Er Yong Chain; Fadillah Ismail (Jurnal Penyelidikan Sains Sosial, 2021)
The social and economic crisis caused by the current COVID-19 outbreak is an extreme but relevant example of the types of challenges leaders face today. It is no secret that the current public health crisis has sent the economy into turmoil, leaving businesses large and small fighting for survival and a workforce living through exceptionally challenging times. Developing leadership in global organizations should be targeted at specific high-leverage skills to give executives the best possible chances for success in the post-coronavirus era. For this reason, this paper is written in an effort to identify the leadership skills needed as a result of experience in facing the crisis and risks of covid-19 as a step forward to compete with the challenge.